A framework for processing business financial rules - Borges, Fernando Cezar R.; Silva, Paulo Caetano da (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
The processing of business rules usually occurs through its encoding in software applications, causing impacts that hinder their maintenance and reuse. In the financial area, the centralization of business rules represented in technology XBRL Formula promotes reuse by multiple applications and reduces these impacts. However, its use is not widespread and solutions that enable the applications reusing business rules with flexibility are restricted to proprietary solutions. This article proposes a framework for flexible processing of business rules defined with XBRL Formula from the use of services.